Alloreactive CD8 T cells rescued from apoptosis during co‐stimulation blockade by Toll‐like receptor stimulation remain susceptible to Fas‐induced cell death. Issue 4 (11th March 2013) - Priyadharshini, Bhavana; Thornley, Thomas B.; Daniels, Keith A.; Cuthbert, Amy; Welsh, Raymond M.; Greiner, Dale L.; Brehm, Michael A.
Summary Blockade of co‐stimulatory signals to T cells is extremely effective for the induction of transplantation tolerance in immunologically naive rodents. However, infections and inflammation compromise the efficacy of co‐stimulation blockade regimens for the induction of tolerance, thereby stimulating the rejection of allografts. Previous studies have shown that stimulation of innate immunity abrogates tolerance induction by preventing the deletion of alloreactive CD8+ T cells that normally occurs during co‐stimulation blockade. Although inflammation prevents the deletion of alloreactive T cells during co‐stimulation blockade, it is not known if this resistance to cell death is the result of a mechanism intrinsic to the T cell. Here, we used syngeneic bone marrow chimeric mice that contain a trace population of T‐cell receptor transgenic alloreactive CD8+ T cells to investigate the early apoptotic signature and activation status of alloreactive T cells following exposure to inflammatory signals during co‐stimulation blockade with an antibody specific for CD154. Our findings revealed that the presence of bacterial lipopolysaccharide during co‐stimulation blockade enhanced the early activation of alloreactive CD8+ T cells, as indicated by the up‐regulation of CD25 and CD69, suppressed Fas ligand expression, and prevented apoptotic cell death. However, alloreactive CD8+ T cells from lipopolysaccharide‐treated mice remained sensitive to Fas‐mediated apoptosis in vitro. These findings suggest that alloreactive T cells rescued from deletion during co‐stimulation blockade by inflammation are still sensitive to pro‐apoptotic signals and that stimulating these apoptotic pathways during co‐stimulation blockade may augment the induction of tolerance.